KARAKTERISTIK BALOK BAMBU LAMINA SUSUN TEGAK DARI BILAH BAMBU ANDONG (Gigantochloa pseudoarundinacea (Steud.) Widjaja) - I.M. Sulastiningsih; Adi Santoso; Krisdianto (Jurnal Penelitian Hasil Hutan, 2016)
The objective of the study was to determine the effect of various layer compositions on the properties of 3-layer vertically glued laminated bamboo beam (LBB). Bamboo strips for LBB fabrication were prepared from mature culms (± 4 years old) of andong bamboo (Gigantochloa pseudoarundinacea (Steud.) Widjaja) collected from private gardens in West Java. The strips were pre-treated by soaking them in 7% boron solution for four hours. Three-layer LBBs were manufactured with six different layer compositions, including bamboo combination with wood planks of manii (Maesopsis eminii Engl.) or sengon (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) as the core layer. The LBB was manufactured using Water Based Polymer-Isocyanate (WBPI) adhesive. The glue spread and cold pressing time applied were 250 g/m and one hour, respectively. Results showed that the average density, moisture content, thickness swelling, and width expansion of LBB were 0.65 g/cm ; 11.1%; 2.09%; and 1.99%, respectively. No delamination occurred in all samples using WBPI adhesive, which indicates high bonding quality. The average bonding strength and percentage bamboo failure (dry test) of LBB were 61.6 kg/cm and 90%, respectively. The physical and mechanical properties of LBB were significantly affected by the layer composition. The presence of wood laminates as the core layer of LBB and the cross wide orientation of the core layer decreased mechanical properties of LBB. On the contrary, the presence of cross-layer in LBB structure increased dimensional stability of the produced LBB.Three-layer thick laminated bamboo beam made of vertically glued andong bamboo strips with various constituted layer composition and all constitued layers laminated together in parallel grain direction had strength values comparable to those of class II of solid wood strength, eventhough the core layer was made of sengon or manii planks.